Evaluating and Ranking of Travel Mode in Metropolitan; A Transportation Economic Approach - Shafiei, Saeid; Vaelizadeh, Raeoof; Bertrand, Frederic; Ansari, Manouchehr (Salehan Institute of Higher Education, 2018)
Nowadays metropolitans' planners faced with a significant growth of private cars and consequently, creation a lot of environmental costs. To tackle the problem, the planners should find the best suitable way with due to the stakeholders’ views and other affected criteria to encourage the passengers for using the public transportation instead of their own cars. This paper has been performed to identifying and verifying main criteria affecting travel mode selection; getting different point of views; identifying the most effective travel mode from stakeholders' point of view and finally evaluating and ranking of travel modes in in Tehran metropolis. This study is a quantitative research based on survey and two structured questionnaires for passengers, experts and managers. In order to have an accurate data analysis, AHP as an MCDM models has been used to evaluate and ranking of travel modes. By identifying main criteria (variables) affecting travel mode selection, also collecting and analyzing stakeholders’ different points of views, the weight of each related criterion has been identified and determined and consequently the priority of effective travel mode in Tehran metropolis has been achieved. Finally, the managerial report has been prepared.